INOVASI SOSIAL DAN TRANSFORMASI PENGELOLAAN SAMPAH NON B3 DALAM MEWUJUDKAN KEWIRAUSAHAAN SOSIAL BERKELANJUTAN (STUDI KASUS PROGRAM CSR SALIN SWARA BADAK LNG) - Putri, Dwi Thia; Sari, Garnis Nurfadila; Wibowo, Putra Peni Luhur; Gunawan, Yuli (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
This article aims to analyze Badak LNG's CSR Salin Swara program in partnership with the Telihan Recycle Garbage Bank in developing social innovations in aluminum non-B3 waste processing. The method used in this study is a qualitative method with a case study approach located in Gunung Telihan Village, West Bontang District, Bontang City, East Kalimantan. The data used uses primary and secondary data originating from internal company data such as social mapping reports, program implementation, program monitoring, and journals, then reduced and triangulated with existing data so that research results can be elaborated more holistically. The results of this study indicate that: 1) The Salin Swara Program through the Telihan Recycle Garbage Bank answers socio-economic and environmental problems in Gunung Telihan Village. This program can answer the problem by turning waste into a resource that can be used to improve the economy. 2) The Telihan Recycle Garbage Bank brings out the transformation of social innovation in managing non-B3 waste into propellers with high economic value and can answer the company's Life Cycle Analysis at the waste management stage. 3) The innovation of the Salin Swara program in the Telihan Recycle Garbage Bank group forms sustainable social entrepreneurship. It encourages an increase in group capability and an increase in beneficiaries' standard of living.